Investigation of the Distribution of Salmonella within an Integrated Pig Breeding and Production Organisation in the United Kingdom. (17th December 2013) - Wales, A.; Weaver, J.; McLaren, I. M.; Smith, R. P.; Mueller-Doblies, D.; Davies, R. H.
Abstract : To examine patterns of Salmonella herd infections in units linked by common sources of pigs, the study examined pooled pen faeces samples from 161 nursery and finishing units in a UK integrated pig enterprise. An epidemiological questionnaire was also completed by investigators for each farm. Salmonella was isolated from 630 (19.5%) of the samples: S. Typhimurium was found in 387 (12%) and S. Derby in 157 (4.9%) samples; 111 units yielded at least one sample containing Salmonella . The proportion of Salmonella -positive samples from positive farms ranged from 5% to 95%. In a univariable risk factor analysis, increasing length of time as a pig farm was positively associated with the detection of Salmonella in a herd. Larger farms (>500 pigs) were significantly more likely to be positive for S. Typhimurium than smaller farms. There was an association between Salmonella serovars isolated in the present study and those subsequently isolated in breeding herds linked to the integration.